Hezi’s Autobiographical Inscription: Philological Study and Interpretation - Stauder-Porchet, Julie (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
Although concise, Hezi’s autobiographical inscription (temp . Teti) displays a number of unusual formulations and a tightly wrought poetic structure. Based on a discussion of various difficult passages, a new translation of the inscription is proposed (part 1). Against the general background of innovative formulation of Teti’s reign, unusual formulations are described as consisting in variations on common formulations, unparalleled phraseology, and grammatical constructions that are not otherwise documented (part 2). The tripartite structure of the text, mirrored in its layout, is examined in relation to the elements of additive and symmetrical patterning that make up the poetic structure of the composition (part 3). Pulling these lines of investigation together, it is finally shown how unusual formulations and poetic structure support one another in foregrounding the semantics of the text (part 4). Rather than narrative and referential, the text is argued to be a form of expository discourse that expresses, or even performatively establishes, aspects of the relation of the speaker with the king.